Seed germination according to crown position and maturation year of Pinus pinaster Ait. closed-cones from Teleno Mountains(León, Northwest Spain) - Molina, C.; Tapias, R.; Gil, L. (Forest Systems, 1997)
Pinus pinaster Ait. from Teleno mountains (NW Spain) has closed-cones. This character has been extensively studied in other pines due to its meaning as a fire adaptative strategy. This paper analyses seed innate dormancy of this pine population. The results indicate that south exposed seeds germinate faster than north or top-crown located seeds. Seed germination rates are correlated to mean daily maximum summer temperature in maturation year. On the contrary, different summer temperatures does not correspond to different percentage of seed viability. We interpret the germination-maturation temperature relation as an efficient mechanism to diversify the length of seed innate dormancy and, in this way, to get an extended germination in time.